Functional Education: An Impetus for Creative Thinking and Sustainable Development of Nigerian Tertiary Institutions - Ariya, Dauda Adeyemo; Ogundele, Michael Olarewaju; Ezeala, Lily Oluebube (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
The paper examined the issues in functional education as an impetus for creative thinking and sustainable development of Nigerian tertiary institutions. The paper further explained the concepts of functional education, creative thinking and sustainable development of tertiary institutions in Nigeria. However, since functional education is essential for creative thinking and sustainable development of Nigerian tertiary institutions the methods of integrative thinking into tertiary institutions programmes and problems militating against effective functional education are also identified. It was therefore concluded that for sustainable national development of Nigerian tertiary institutions, functional educational approach such as curriculum diversification, manipulative skills, should be used through questioning and activity and child-centerednessÂ’ oriented methods should be used in the schools system. Suggestions were preferred for the effective functional education practices to be used in order to enhance creative thinking for a sustainable development of Nigerian tertiary institution. Keywords : Functional education, creative thinking, sustainable development and Nigerian tertiary institutions.